Tanggung Jawab Terhadap Pendidikan Anak: Analisis Kitab Tarbiyatul Aulad Fil Islam Karangan Abdullah Nashih Ulwan - rambe, sari madani rambe; Wahyudi, Hakmi (GHIROH, 2024)
The objective of this article is to explore comprehensively the obligations related to the education of children from the standpoint of Abdullah Nashih Ulwan as portrayed in his publication "Tarbiyatul Aulad Fi Al-Islam", whilst examining the assorted obligations outlined by Ulwan in his publication. This investigation utilizes a qualitative approach concentrating on a review of literature, with the intention of capturing the core of Abdullah Nashih Ulwan's ideologies. The research results reveal that Ulwan recognizes seven categories of obligations towards children's education, encompassing faith-based, ethical, physical, cognitive, emotional, communal, and sexual education. This educational process can be executed both in the familial setting, where both parents act as instructors, and in the school atmosphere, where educators assume a principal role in the educational journey.